O ROMANCE: INTERAÇÕES E INTER-RELAÇÕES NAS TEORIAS DE GOLDMANN E BAKHTIN - Pereira, Marcos Aparecido; Magalhães, Epaminondas de Matos (Revista Areia, 2023)
This essay discusses the novel from the perspective of Lucien Goldmann and Mikhail Bakhtin, looking at their thought basis for understanding this genre from different perspectives of study and, therefore, seeking to comprehend the novel and its interaction and interrelation with the human being and his world.